1976
DOI: 10.1007/bf01937791
|View full text |Cite
|
Sign up to set email alerts
|

Struktur-Wirkungsbeziehungen beim menschlichen Calcitonin. III. Die biologische Aktivität verkürzter oder an den Kettenenden modifizierter, synthetischer analoger

Abstract: Assays of 8 synthetic analogues of human calcitonin in rats showed that their hypocalcaemic activity was drastically reduced by deletion of the C-terminal amide group, chain-shortening or opening of the disulphide ring, but unaffected or enhanced by modification of the N-terminal amino group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 5 publications
0
23
0
Order By: Relevance
“…This is further evidence for the evolution of human calcitonin to an intrinsically less potent form of the hormone. Substitutions of amino acids in the structure of human calcitonin towards the structure of the salmon hormone results in a potentiation of the affinity and potency of the human hormone in the 8866 cells, which reasonably well agree with their hypocalcemic activity (10,(15)(16)(17)(18). We cannot exclude the existence of separate high-affinity binding sites for labeled human or porcine calcitonins that are not detected with salmon 125I-calcitonin.…”
Section: Methodsmentioning
confidence: 67%
See 2 more Smart Citations
“…This is further evidence for the evolution of human calcitonin to an intrinsically less potent form of the hormone. Substitutions of amino acids in the structure of human calcitonin towards the structure of the salmon hormone results in a potentiation of the affinity and potency of the human hormone in the 8866 cells, which reasonably well agree with their hypocalcemic activity (10,(15)(16)(17)(18). We cannot exclude the existence of separate high-affinity binding sites for labeled human or porcine calcitonins that are not detected with salmon 125I-calcitonin.…”
Section: Methodsmentioning
confidence: 67%
“…In Fig. 5 the relative binding inhibition of the various calcitonins and their relative ability to stimulate cAMP accumulation is compared to their hypocalcemic activity (10,(15)(16)(17)(18). The concentrations of calcitonin causing half-maximal inhibition of binding and halfmaximal stimulation of cAMP formation were comparable and corresponded reasonably well to their hypocalcemic activity.…”
Section: Methodsmentioning
confidence: 81%
See 1 more Smart Citation
“…Studies correlating calcitonin structure with function have demonstrated that an intact disulfide bridge between sequence positions 1 and 7 of the monomer is essential for biological activity (37), and, indeed, the dimer previously extracted from tumor tissue was demonstrated to have little activity until converted to monomer (38). This, therefore, may explain the absence of detectable activity in pool I in which the intramolecular disulfide bridge would no longer have remained intact.…”
Section: Resultsmentioning
confidence: 99%
“…Any shortening or modification at the carboxyl end leads to loss of this biologic activity (19). Structural modifications at the N-terminus have no effect (20), whereas opening of the disulfide ring abolishes the biologic activity (21).…”
Section: Chemistry Of Calcitoninmentioning
confidence: 99%